ANALYSIS OF WORK STRESS AMONG TEACHERS OF SELF FINANCING COLLEGES IN KOTTAYAM DISTRICT, KERALA - LIGI JOLLY (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE & MANAGEMENT, 2014)
The phenomenon of work stress among teachers of self financing colleges has been receiving increased global attention and concern in recent years. Teaching has now become a very demanding occupation with a lot of stresses for a teacher who has a lot of deadlines to meet and a lot of responsibilities to shoulder besides teaching a child what are in a text book. It is important to tackle the causes of stress in the workplace as stress at work can lead to problems for the individual, working relationships and the overall environment. These issues may include lowered self esteem and poor concentration skills for the employees. Managing stress in the workplace is therefore an essential part of both individual and it is institutional social responsibility also. The present study was undertaken to analyze the types of stress among the faculty members in self financing colleges in and around Kottayam district of Kerala state. The study aims at identifying the stress creators among the faculty members.